2002
DOI: 10.2337/diacare.25.12.2212
|View full text |Cite
|
Sign up to set email alerts
|

Bimodality in Blood Glucose Distribution

Abstract: OBJECTIVE -Bimodality in blood glucose (BG) distribution has been demonstrated in several populations with a high prevalence of diabetes and obesity. However, other population studies had not found bimodality, thus casting doubt on its universality. We address this question in four ethnic populations-namely Malay, Chinese, Indian, and the indigenous people of Borneo. RESEARCH DESIGN AND METHODS -A national health survey was conducted inMalaysia in 1996. A total of 18,397 subjects aged Ն30 years had post-challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…According to these criteria, values above the nadir are indicative of diabetes, whereas values below the nadir are not. In the present study, the nadir of postchallenge glucose (the cut point that separates the two components) was in the range of 11.1-13.6 mmol/l, which was slightly higher than the diabetes diagnostic criteria recommended by the World Health Organization in 1985 (9), but similar to the 2-h glucose nadirs found in a recent Malaysian study of four ethnic groups (17) and in Egyptians (18).…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…According to these criteria, values above the nadir are indicative of diabetes, whereas values below the nadir are not. In the present study, the nadir of postchallenge glucose (the cut point that separates the two components) was in the range of 11.1-13.6 mmol/l, which was slightly higher than the diabetes diagnostic criteria recommended by the World Health Organization in 1985 (9), but similar to the 2-h glucose nadirs found in a recent Malaysian study of four ethnic groups (17) and in Egyptians (18).…”
Section: Methodssupporting
confidence: 71%
“…Other biases that could obscure bimodality of type 1 and type 2 diabetes or admixture in white cohorts include the exclusion of persons with known diabetes who refuse or are not offered a glucose tolerance test (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the estimated cut points were inconsistent between countries, especially for 2-h plasma glucose when participants with known diabetes were included. Comparing these results with those of earlier studies, we found that the overall cut point for FPG was somewhat lower (2,3,8,9), whereas the cut point for 2-h plasma glucose was well in line (1)(2)(3)5,8,10,11,13), except for the studies of South African Indians (9) and Western Samoans (12), which produced lower cut points for 2-h plasma glucose.…”
Section: -Distribution Of Fpg In Korea (A) and Nauru (B) And 2-h Plassupporting
confidence: 77%
“…This exclusion potentially makes the two components less distinct and thereby decreases the probability of a meaningful cut point separating them. However, as acknowledged in previous studies (3,10,13), including patients with known diabetes in the analyses will induce a treatment bias for the following reasons. In accordance with existing treatment guidelines, patients with diabetes are treated with the aim of lowering their glucose to a near-normal range.…”
Section: -Distribution Of Fpg In Korea (A) and Nauru (B) And 2-h Plasmentioning
confidence: 99%